Preparation method of high-compaction-density composite sodium ferric phosphate positive electrode material

By using graded iron sources and organic acids, a composite sodium iron phosphate cathode material with close packing and uniform carbon coating was formed, solving the problem of low compaction density and enabling high energy density and low cost sodium-ion battery applications.

CN120864468AActive Publication Date: 2025-10-31JIANGSU BTR NANO TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511392832.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-27
Publication Date
2025-10-31
Estimated Expiration
2045-09-27

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively improve the compaction density of composite sodium iron phosphate cathode materials, which limits the energy density of sodium-ion batteries and the cost per watt-hour of the cells.

Method used

A graded iron source and organic acid are mixed with water and ground, spray-dried, and then calcined at high temperature under inert gas protection to form a composite sodium iron phosphate cathode material with a tightly packed structure and a uniformly coated carbon layer on the surface.

Benefits of technology

The compaction density of the composite sodium iron phosphate cathode material was significantly increased to 2.30-2.36 g/cm3, which improved the energy density of the sodium battery cell and reduced the production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120864468A_ABST
    Figure CN120864468A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-compaction-density composite sodium iron phosphate positive electrode material, which comprises the following steps: mixing and grinding a graded iron source, a sodium source, a phosphorus source and a carbon source, adding an organic acid, uniformly mixing, spray-drying, and calcining to form the closely-packed composite sodium iron phosphate positive electrode material with the surface uniformly coated with a carbon layer. According to the preparation method, the compaction density of the NFPP material can be effectively improved and reaches 2.30-2.36 g / cm < 3 >, the energy density of a sodium cell is improved, and the production cost of a sodium battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery cathode material preparation, and particularly relates to a method for preparing a high-density composite sodium iron phosphate cathode material. Background Technology

[0002] Polyanionic composite sodium iron phosphate (NFPP), as a cathode material for sodium-ion batteries, possesses a unique three-dimensional framework structure, providing a broad tunnel network for sodium ion transport. It exhibits a volume change of less than 4% during charge and discharge, long cycle life, a high voltage plateau (3.2V) and specific capacity (up to 129mAh / g), and excellent low-temperature performance, making it a high-performance and cost-effective material. Therefore, it has become a research hotspot and development direction for cathode materials in sodium-ion batteries.

[0003] However, in practical applications, the compaction issue of NFPP limits its performance improvement. The material has a low compaction density in its natural state, typically ranging from 1.95 to 2.15 g / cm³. 3 Its true density is 3.2 g / cm³. 3 Compared to the current mainstream lithium iron phosphate (LFP) materials with a density of 2.45-2.6 g / cm³, this is significantly better. 3 Its true density is 3.6 g / cm³. 3 This greatly limits the energy density in sodium battery applications and increases the cost per watt-hour of the battery cell.

[0004] Existing technology CN118083938A discloses a method for preparing composite sodium iron phosphate with flexible adjustment of compaction and electrical properties. This method involves dispersing iron source 1, iron source 2, phosphorus source, sodium source, surfactant, and carbon source in water to form a uniform slurry. Iron source 1 is FePO4, and iron source 2 is NH4Fe2(OH)(PO4)2·2H2O. The resulting slurry is then subjected to multi-stage grinding, spray drying, and finally sintering under an inert atmosphere to obtain composite sodium iron phosphate. This existing technology uses two types of FePO4, which are calcined at high temperatures, resulting in primary particle melting. The grinding process using a sand mill to prepare the target product is time-consuming and has higher FePO4 raw material costs. Furthermore, the other iron source 2 presents significant challenges in controlling the synthesis process, which greatly affects the mass production of the product and makes large-scale production difficult. Additionally, iron source 2 contains ammonium ions (NH4+). + The continuous release of NH3 gas during sand milling and spraying aggravates pollution of the production environment and water bodies, and increases production control costs. In particular, the spraying process makes it easy for NH3 gas to escape, affecting the surrounding industrial environment, or further adding corresponding equipment for environmental protection treatment, which further increases costs.

[0005] Existing technology CN119637837A discloses a method for preparing a high-compact-density composite sodium iron phosphate cathode material, comprising the following steps: sodium, iron, and phosphorus sources for preparing the composite sodium iron phosphate cathode material are metered, mixed, and ground according to the chemical formula Na4Fe3(PO4)2P2O7, while simultaneously adding 8% by mass of a carbon source to obtain a precursor aqueous solution; a surfactant is added to the precursor aqueous solution, and the mixture is ground and mixed uniformly to obtain a homogeneous precursor aqueous solution; the homogeneous precursor aqueous solution is dried and granulated using spray drying technology to obtain composite sodium iron phosphate precursor particles; the composite sodium iron phosphate precursor particles are subjected to high-temperature heat treatment under inert gas protection to obtain the composite sodium iron phosphate cathode material. This invention mainly utilizes surfactants to prepare a homogeneous precursor to obtain a higher-purity composite sodium iron phosphate cathode material. However, it cannot progressively optimize compaction density from the first principles; it only optimizes the purity of the product, and it is difficult to achieve the "close packing principle" of particles to improve compaction density.

[0006] Based on this, we are now developing a method to improve the compaction density of composite sodium iron phosphate material. As a positive electrode for sodium-ion batteries, its application in sodium-ion batteries can improve their energy density and reduce production costs, which is of great significance. Summary of the Invention

[0007] Objective of the invention: The technical problem to be solved by the present invention is to provide a method for preparing a composite sodium iron phosphate cathode material. This method can effectively improve the density of the prepared cathode material and achieve uniform carbon coating during preparation, thereby improving conductivity while increasing density.

[0008] Technical solution: The preparation method of the high-density composite sodium iron phosphate cathode material of the present invention includes the following steps:

[0009] (1) After measuring the sodium source, iron source, and phosphorus source according to the chemical formula Na4Fe3(PO4)2P2O7, add the carbon source, mix and grind with water to obtain a precursor slurry; wherein, the iron source includes small particles and large particles with a weight ratio of (5-7):(5-3), and the iron source is selected from ferrous oxalate, ferric carbonate, ferric phosphate or ferric phosphate dihydrate;

[0010] (2) Add organic acid to the precursor slurry, grind and mix evenly to obtain a homogeneous precursor slurry;

[0011] (3) The homogeneous precursor slurry was granulated by spray drying to obtain composite sodium iron phosphate precursor particles;

[0012] (4) The composite sodium iron phosphate precursor particles are subjected to high-temperature calcination under inert gas protection to obtain the composite sodium iron phosphate cathode material.

[0013] Furthermore, in step (1), the iron source is non-dissolved raw material iron source particles (the main factor affecting compaction density), preferably ferric phosphate dihydrate. Using ferric phosphate dihydrate retains the smallest particle size, avoiding the melting and growth of particles during the dehydration process of anhydrous ferric phosphate preparation, directly avoiding the melting phenomenon between particles, which can greatly shorten the grinding time and improve the grinding efficiency in the grinding process, which is beneficial to improving the electrical properties and rate performance of composite sodium iron phosphate.

[0014] Furthermore, in step (1), the iron source is graded particles with the following particle size distribution: small particles are controlled with D10≤150nm, D50≤400nm, D90≤700nm, and Dmax<1.2μm; large particles are controlled with a particle size of 0.7μm. <D10<1.0μm,2μm<D50<6μm,8μm<D99<11μm,Dmax<15μm。

[0015] Furthermore, in step (2), the organic acid is selected from acetic acid, propionic acid, succinic acid, malonic acid, DL-lactic acid, glycine, and isovaleric acid.

[0016] Furthermore, in step (2), the organic acid mass is 0.3-5% of the mass of the precursor slurry.

[0017] Furthermore, in step (2), the average particle size of the homogeneous precursor slurry is 0.1μm-0.4μm, and the solid content of the homogeneous precursor slurry is 25-60%.

[0018] Furthermore, in step (3), the spray drying temperature is 180-260°C, and the atmosphere is one of air, nitrogen, or argon.

[0019] Furthermore, in step (4), the high-temperature calcination temperature is 400-550℃, the calcination time is 5-15 h, the inert gas is either nitrogen or argon, and the heating rate is 3℃ / min-12℃ / min.

[0020] Furthermore, in step (1), the sodium source is selected from sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium pyrophosphate, sodium citrate, trisodium phosphate, sodium acetate, and sodium oxalate; the phosphorus source is selected from phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, iron phosphate, sodium pyrophosphate, and trisodium phosphate; and the carbon source is selected from glucose, sucrose, ascorbic acid, chitosan, polyvinylamine, polyacrylamide, citric acid, polyethylene glycol, lignin, and nanocellulose.

[0021] Beneficial effects: Compared with the prior art, the significant advantages of this invention are: using a graded iron source, and after adding organic acid for uniform dispersion, spray drying and calcination form a tightly packed composite sodium iron phosphate cathode material with a uniformly coated carbon layer on the surface, thereby increasing the compaction density of the NFPP material (2.30-2.36 g / cm³). 3 This increases the energy density of sodium cells and reduces the production cost of sodium batteries. Attached Figure Description

[0022] Figure 1 SEM image of the sintered NFPP material sample prepared in Example 1;

[0023] Figure 2 SEM image of NFPP material after air jet milling, as shown in Example 1;

[0024] Figure 3 SEM images of sintered NFPP material samples prepared in Example 2;

[0025] Figure 4 SEM image of NFPP material after air jet milling, as shown in Example 2;

[0026] Figure 5 SEM image of the sintered NFPP material sample prepared in Example 3;

[0027] Figure 6 SEM image of NFPP material after air jet milling, as shown in Example 3;

[0028] Figure 7 SEM image of the sintered NFPP material sample prepared in Example 4;

[0029] Figure 8 SEM image of NFPP material after air jet milling, as shown in Example 4;

[0030] Figure 9 SEM image of the sintered NFPP material sample prepared in Example 5;

[0031] Figure 10 SEM image of NFPP material after air jet milling, as shown in Example 5;

[0032] Figure 11 This is a SEM image of the sintered NFPP material sample prepared in Example 6;

[0033] Figure 12 SEM image of NFPP material after air jet milling, as shown in Example 6;

[0034] Figure 13 SEM image of the sintered NFPP material sample prepared in Example 7;

[0035] Figure 14 SEM image of NFPP material after air jet milling, as shown in Example 7;

[0036] Figure 15 SEM image of the sintered NFPP material sample prepared in Example 8;

[0037] Figure 16 SEM image of NFPP material after air jet milling, as shown in Example 8;

[0038] Figure 17 SEM images of sintered NFPP material samples prepared for Comparative Example 1;

[0039] Figure 18 SEM image of NFPP material after air jet milling, for Comparative Example 1;

[0040] Figure 19 SEM images of sintered NFPP material samples prepared for Comparative Example 2;

[0041] Figure 20 SEM images of NFPP material after air jet milling were prepared for Comparative Example 2;

[0042] Figure 21 SEM images of sintered NFPP material samples prepared for Comparative Example 3;

[0043] Figure 22 SEM images of NFPP material after air jet milling were prepared for Comparative Example 3. Detailed Implementation

[0044] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be noted that all raw materials used in the present invention are commercially available.

[0045] The specific particle size distribution of the graded iron source used in Examples 1-8 and Comparative Examples 2-3 of this invention is as follows: the weight ratio of small particles to large particles is 6:4. Specifically, the particle size of the small particles is controlled within the range of D10≤150nm, D50≤400nm, D90≤700nm, and Dmax<1.2μm; the particle size of the large particles is controlled within the range of 0.7μm. <D10<1.0μm,2μm<D50<6μm,8μm<D99<11μm,Dmax<15μm。

[0046] Example 1

[0047] Example 1 uses graded ferric phosphate as the iron source to prepare a composite sodium iron phosphate material with the molecular formula Na4Fe3P4O. 15 It is prepared by the following steps:

[0048] (1) Based on the stoichiometric ratio of Na, Fe and P elements in the chemical formula Na4Fe3(PO4)2P2O7, and the molar ratio of Na, Fe and P in the final product of 4:3:4, calculate and weigh the main raw materials, add graded ferric phosphate, disodium hydrogen phosphate dodecahydrate, sodium acetate trihydrate and citric acid to water, and stir magnetically for 15 min to obtain the precursor slurry.

[0049] (2) Add 1.5% of propionic acid to the precursor slurry, grind in a coarse grinding jar for 10 min, then transfer to a sand mill and grind at a speed of 1800 r / min. Adjust the grinding chamber temperature to <30℃ and grind for about 30 min. After grinding, control the slurry particle size. The particle size distribution D50 is 250-320 nm, the average particle size is 0.305 μm, the viscosity of the slurry is <100 mpa*s, and the solid content of the homogeneous precursor slurry is 42%.

[0050] (3) The slurry is spray-dried in a spray drying tower with an inlet temperature of 230℃ and an outlet temperature of 105±5℃. The powder is obtained by spray drying. The particle size of the powder after spray drying is controlled as follows: D10: 5-10 μm, D50: 25-33 μm, D99: 45-60 μm.

[0051] (4) The powder was transferred to a tube furnace and calcined at 500°C at a rate of 12°C / min under a nitrogen protective atmosphere for 10 h. The sintered material was then allowed to cool naturally to obtain the sintered material. The sintered compaction density was measured, and scanning electron microscopy (SEM) images were taken simultaneously. See attached images. Figure 1 As shown.

[0052] (5) The final target powder particle size of sodium iron phosphate was obtained by air jet milling: D10: 0.6-1 μm, D50: 4-5 μm, D99: 20-30 μm. The compaction density was measured and SEM images were taken. See [link to SEM image]. Figure 2 As shown.

[0053] Example 2

[0054] The preparation method in Example 2 is basically the same as that in Example 1, except that the iron source is graded ferric phosphate dihydrate. The SEM images of the sintered materials are shown below. Figure 3 As shown, the SEM image after airflow pulverization is as follows. Figure 4 As shown.

[0055] Example 3

[0056] The preparation method in Example 3 is basically the same as that in Example 1, except that the iron source is graded ferrous oxalate. The SEM images of the sintered materials are shown below. Figure 5 As shown, the SEM image after airflow pulverization is as follows. Figure 6 As shown.

[0057] Example 4

[0058] The preparation method in Example 4 is basically the same as that in Example 1, except that the iron source is graded iron carbonate, and the SEM image of the sintered material obtained is shown in Figure 7 the SEM image after air jet milling is shown in Figure 8 as follows.

[0059] Example 5

[0060] The preparation method in Example 5 is basically the same as that in Example 1, except that the organic acid is malonic acid, and the SEM image of the sintered material obtained is shown in Figure 9 the SEM image after air jet milling is shown in Figure 10 as follows.

[0061] Example 6

[0062] The preparation method in Example 6 is basically the same as that in Example 1, except that the organic acid is succinic acid, and the SEM image of the sintered material obtained is shown in Figure 11 the SEM image after air jet milling is shown in Figure 12 as follows.

[0063] Example 7

[0064] The preparation method in Example 7 is basically the same as that in Example 1, except that the organic acid is DL-lactic acid, and the SEM image of the sintered material obtained is shown in Figure 13 the SEM image after air jet milling is shown in Figure 14 as follows.

[0065] Example 8

[0066] The preparation method in Example 8 is basically the same as that in Example 1, except that the organic acid is isovaleric acid, and the SEM image of the sintered material obtained is shown in Figure 15 the SEM image after air jet milling is shown in Figure 16 as follows.

[0067] Comparative Example 1

[0068] The preparation method in Comparative Example 1 is basically the same as that in Example 1, except that the iron source is conventional iron phosphate with a particle size of 4μm < D50 < 6μm and no organic acid is added. The SEM image of the sintered material obtained is shown in Figure 17 the SEM image after air jet milling is shown in Figure 18 as follows.

[0069] Comparative Example 2

[0070] The preparation method in Comparative Example 2 is basically the same as that in Example 3, except that the iron source is graded ferrous oxalate and no organic acid is added. The SEM images of the sintered materials are shown below. Figure 19 As shown, the SEM image after airflow pulverization is as follows. Figure 20 As shown.

[0071] Comparative Example 3

[0072] The preparation method in Comparative Example 3 is basically the same as that in Example 1, except that the iron source is graded ferrous carbonate and an organic acid is added. The SEM images of the sintered materials are shown below. Figure 21 As shown, the SEM image after airflow pulverization is as follows. Figure 22 As shown.

[0073] Cathode material performance testing

[0074] The prepared positive electrode material (active material), conductive agent (Super P), and binder (PVDF) were weighed at a mass ratio of 95:5:5. An appropriate amount of NMP was added as a solvent, and the mixture was continuously and thoroughly ground. The ground slurry was then evenly and smoothly coated onto an aluminum foil current collector. After drying, it was cut into discs with a diameter of 1.2 cm. A coin cell was assembled using the positive electrode discs, separator, sodium metal negative electrode, and sodium-ion battery electrolyte. The battery was charged and discharged within a voltage window of 1.5–4.0 V, cycled twice at 0.1 C, and then cycled more than twice at 1 C. Data from all examples and comparative examples are shown in Table 1.

[0075] Table 1 Material Performance Indicators

[0076] Example <![CDATA[Sintered Compaction Density (g / cm 3 )]]> <![CDATA[Apparent density of powder (g / cm 3 )]]> 0.1C charging specific capacity (mAh / g) 0.1C discharge specific capacity (mAh / g) 1C discharge specific capacity (mAh / g) 1C / 0.1C Example 1 2.23 2.32 121.19 113.75 107.66 0.9465 Example 2 2.28 2.35 119.36 110.59 106.39 0.9620 Example 3 2.30 2.36 120.53 111.53 105.36 0.9447 Example 4 2.25 2.34 120.06 108.04 104.18 0.9643 Example 5 2.24 2.32 121.13 110.03 105.77 0.9613 Example 6 2.27 2.33 120.77 110.35 104.07 0.9431 Example 7 2.22 2.30 120.12 109.94 106.89 0.9723 Example 8 2.21 2.30 119.14 108.76 105.76 0.9724 Comparative Example 1 1.98 2.09 114.31 103.76 95.32 0.9187 Comparative Example 2 2.05 2.14 113.92 103.22 94.79 0.9183 Comparative Example 3 2.10 2.16 114.01 101.86 93.97 0.9225

[0077] As can be seen from Table 1, the sintering compaction density and powder compaction density of Examples 1-8 are much higher than those of Comparative Examples 1-3, with the highest powder compaction reaching 2.36 g / cm³. 3 Furthermore, as shown in Table 1, under high powder compaction density, the charge / discharge specific capacity is significantly higher than that of Comparative Examples 1-3, and the 1C / 0.1C rate retention rate is also higher than that of Comparative Examples 1-3. This indicates that the present invention achieves high compaction density and maintains good capacity characteristics at high rates only through simultaneous control of the iron source, its gradation, and the organic acid.

[0078] Figure 1-16 As shown, from the SEM morphology of the materials, the sintered samples of Examples 1-8 exhibit a dense, molten surface with few or very small pores, indicating that the spheres are in a close-packed state. However, after airflow pulverization, the particles are all irregular large particles composed of primary particle adhesion and molten state, forming a uniform surface carbon coating. Furthermore, Figure 17-22As shown, the SEM surface of the sintered samples in Comparative Examples 1-3 is relatively loose with many pores, indicating that there are many gaps between the primary particles of the spheres, suggesting relatively low compaction. After airflow pulverization, the particles are all large, irregular particles formed by loose floating carbon deposits between the primary particles.

[0079] Based on the above experimental data, further analysis from a mechanistic perspective reveals that this invention employs iron source particles with different gradations. By controlling the particle size and distribution of the main raw material, iron source particles with different gradations can stack and fill the gaps between particles. During the calcination preparation of composite sodium iron phosphate, the "close packing principle" (small particles fill the gaps between large particles) is followed, reducing the gaps between particles and achieving a gradation effect between particle sizes, thereby further improving the compaction density of the product.

[0080] Furthermore, organic acids are introduced during the preparation process and mixed uniformly with the precursor slurry. The addition of these organic acids reduces the viscosity of the slurry during grinding and mixing, promoting uniform distribution of raw materials, reducing micropores within the particles, and decreasing specific surface area and porosity, ultimately optimizing the crystal orientation and morphology of NFPP. On the other hand, it facilitates the simultaneous optimization of the primary nanoparticle iron source particle size distribution during sintering, enabling easier and better melting and growth into a multi-layered eutectic. This ensures good electronic conductivity of the primary particles while maintaining a close-packed structure, while still maintaining a small specific surface area, reduced porosity, and fewer voids during packing, ultimately achieving higher compaction density. In addition, the addition of organic acids, through the interaction between the carboxyl or hydroxyl groups on the organic acid and the hydroxyl groups of the carbon source, achieves uniform dispersion of the solid carbon source particles using water-soluble organic acids, resulting in uniform dispersion of the carbon source during spray drying and improving the uniformity of carbon coating.

[0081] In other words, the preparation method of the present invention can improve the density and simultaneously achieve uniform carbon coating, thereby effectively avoiding the side effects of reduced porosity and longer ion diffusion paths caused by increased density, which would affect electrochemical performance.

[0082] In addition to the above embodiments, it should be noted that the carbon content of the cathode material prepared by the present invention can reach 1.5-2.0%, and this content can be adaptively adjusted by the amount of carbon source added.

[0083] Furthermore, the sodium source used in preparing the composite sodium iron phosphate cathode material according to this invention can also be selected from sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium pyrophosphate, sodium citrate, trisodium phosphate, and sodium oxalate. The phosphorus source can be selected from phosphoric acid, ammonium dihydrogen phosphate, iron phosphate, sodium pyrophosphate, and trisodium phosphate. The lithium source can also be selected from lithium hydroxide, lithium sulfate, lithium nitrate, or lithium chloride precursors. The carbon source can be selected from sucrose, ascorbic acid, chitosan, polyvinylamine, polyacrylamide, polyethylene glycol, lignin, and nanocellulose. The organic acid content can be 0.3-5% of the mass of the precursor slurry.

[0084] The technical effects claimed by this invention can be achieved by using the preparation process and the parameter range defined in this invention, so no further examples will be given to support this claim.

Claims

1. A method for preparing a high-density composite sodium iron phosphate cathode material, characterized in that, Includes the following steps: (1) After measuring the sodium source, iron source, and phosphorus source according to the chemical formula Na4Fe3(PO4)2P2O7, add the carbon source, mix and grind with water to obtain a precursor slurry; wherein, the iron source includes small particles and large particles with a weight ratio of (5-7):(5-3), and the iron source is selected from ferrous oxalate, ferric carbonate, ferric phosphate or ferric phosphate dihydrate; (2) Add organic acid to the precursor slurry, grind and mix evenly to obtain a homogeneous precursor slurry; (3) The homogeneous precursor slurry was granulated by spray drying to obtain composite sodium iron phosphate precursor particles; (4) The composite sodium iron phosphate precursor particles are subjected to high-temperature calcination under inert gas protection to obtain the composite sodium iron phosphate cathode material.

2. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the particle size distribution of the iron source is as follows: the particle size of small particles is controlled within D10≤150nm, D50≤400nm, D90≤700nm, and Dmax<1.2μm; the particle size of large particles is controlled within 0.7μm. <D10<1.0μm,2μm<D50<6μm,8μm<D99<11μm,Dmax<15μm。 3. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the organic acid is selected from acetic acid, propionic acid, succinic acid, malonic acid, DL-lactic acid, glycine or isovaleric acid.

4. The method for preparing the composite sodium iron phosphate cathode material according to claim 1 or 3, characterized in that, In step (2), the amount of organic acid added is 0.3-5% of the mass of the precursor slurry.

5. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (2), the average particle size of the homogeneous precursor slurry is 0.1-0.4 μm, and the solid content of the homogeneous precursor slurry is 25-60%.

6. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (3), the spray drying temperature is 180-260℃, and the atmosphere is one of air, nitrogen, or argon.

7. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (4), the high-temperature calcination temperature is 450-550℃, the calcination time is 5-15 h, the inert gas is either nitrogen or argon, and the heating rate is 3℃ / min-12℃ / min.

8. The method for preparing the composite sodium iron phosphate cathode material according to claim 1, characterized in that, In step (1), the sodium source is selected from sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium pyrophosphate, sodium citrate, trisodium phosphate, sodium acetate, and sodium oxalate; the phosphorus source is selected from phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, iron phosphate, sodium pyrophosphate, and trisodium phosphate; and the carbon source is selected from glucose, sucrose, ascorbic acid, chitosan, polyvinylamine, polyacrylamide, citric acid, polyethylene glycol, lignin, and nanocellulose.

Citation Information

Patent Citations

  • Composite sodium ferric phosphate positive electrode material with high compaction density, preparation method of composite sodium ferric phosphate positive electrode material and application of composite sodium ferric phosphate positive electrode material in sodium ion battery

    CN119637837A

  • Preparation method of ferric sodium pyrophosphate capable of flexibly adjusting compaction and electrical properties

    CN118083938A

  • Iron-based sodium pyrophosphate / C composite material and preparation and application thereof in sodium ion battery

    CN118108202A

  • Carbon-coated ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof

    CN118213528A

  • Pyrophosphate ferric phosphate sodium positive electrode material and preparation method and application thereof

    CN120246972A